Impact of different types of storage media on enamel surface roughness and granularity distribution of avulsed teeth (In vitro study) - Obeid , Rawaa S; Khalaf, Muna S (Journal of Baghdad College of Dentistry, 2022)
Background: To investigate the effect of different types of storage media on enamel surface microstructure of avulsed teeth by using atomic force microscope.Materials and methods : Twelve teeth blocks from freshly extracted premolars for orthodontic treatment were selected . The study samples were divided into three groups according to type of storage media :A-egg white , B- probiotic yogurt , and C-bovine milk . All the samples were examined for changes in surface roughness and surface granularity distribution using atomic force microscope, at two periods: baseline, and after 8 hours of immersing in the three types of storage media. Results: Milk group had showed a significant increase in the mean of the roughness values at the test period, while the egg white and the probiotic yogurt groups showed decrease in the surface roughness at the test period. No significant changes was found in the grain size of enamel surface of the avulsed tooth in any types of three storage media at eight hours interval. The use of egg white and probiotic yogurt to store the samples may be beneficial in that they contain various ions and proteins that fill up enamel valleys, while the longer periods of milk exposure encourage the bacteria to continue fermenting lactose, resulting in continual acid generation and increased demineralization. Conclusion : Milk group demonstrated the highest roughness values, while the egg white group demonstrated the lowest roughness values of the teeth. No significant changes in the grain size of enamel surface of the tested teeth in any types of three storage media at eight hours interval .